Hubungan Menyendawakan Setelah MenyusuiDengan Kejadian Regurgitasi Pada Bayi Usia0 - 6 Bulan Di Kelurahan NoborejoKota Salatiga - Evrida Samsuri, Aulia; , Irdawati, S.kep.,Ns.,M.Si.Med (2016)
Breastfeeding is staple food required childern aged 0-6 months, After the baby suckling let burping first to expelling air who to enter when baby suckling. Breastfeeding also can make the impact in infants one of them is regurgitation for a moment after baby drink breastfeeding.Research aims to understand relations burping an infant by events regurgitation in infants 6-0 months in Kelurahan Noborejo Salatiga city .Design this research is diskriptif the correlation with have the cross-sectional. Population this research is mother having children aged 6-0 months in urban Kelurahan Noborejo Salatiga city with the sample of the 50 mother children aged 6-0 months to technique the sample collection total of sampling. Instrument data collection uses a questionnaire and analysis of data was undertaken using analysis correlation gamma and somers. He research results show baby 6-0 months most burping in the category of good with 30 respondents ( 60 % ) . he incident regurgitation in infants 6-0 months some larger category rarely with 31 respondents ( 62 % ). There was a correlation burping an infant by events regurgitation in infants 6-0 months in urban Kelurahan Noborejo Salatiga city, with p value = -0, 000. Let mother who have babies increase the knowledge about how burping baby right and increase awareness of the importance of burping after feeding as effort to prevent regurgitation.